ChemInform Abstract: Synthesis, Structural and Magnetic Characterization of the Fluorinated Compound 15R‐BaFeO2F. Issue 34 (1st August 2013) - Clemens, Oliver; Berry, Frank J.; Bauer, Jessica; Wright, Adrian J.; Knight, Kevin S.; Slater, Peter R.
Abstract 15R‐BaFeO2F (I) and 15R‐BaFeO2.27F0.5 (II) are prepared by low temperature fluorination of the precursor 15R‐BaFeO3‐dF0.2 (III) using polyvinylidenedifluoride as a fluorination agent.